Circular Economy Implementation in Community-Based Plastic Waste Management: A Case Study of Waste Bank Amal Haqiqi Garut, Indonesia: An Analysis of Community-Based Plastic Waste Management for Creating Sustainable Environment - Nurfitriyani Purnamasari; Gemilang Lara Utama; Rizky Ramadhan (Industrial and Domestic Waste Management, 2026)
Waste banks represented a pivotal form of community-based waste management with the potential to operationalize circular economy principles by integrating social, environmental, economic, and technical dimensions. However, empirical verification through systematic performance measurement was essential to validate their effectiveness. This study aimed to analyze the implementation of a circular economy system in plastic waste management at Bank Sampah Amal Haqiqi, located in Bayongbong, Garut. The research first utilized Material Flow Analysis (MFA) to quantify the flow and transformation of plastic waste. Subsequently, the Analytical Hierarchy Process (AHP) was employed to evaluate management performance based on 11 stakeholder perspectives across four criteria: social, environmental, economic, and technical aspects. The AHP results were validated using a Consistency Ratio (CR) of ≤ 0.10. The MFA revealed a plastic waste recycling rate of 76%, with a residue rate of 3.7%. The AHP weighting identified the social criterion as the highest priority (0.33), followed by the technical criterion (0.30). These findings highlighted that management success was predominantly driven by human factors and operational infrastructure. The implementation of a circular economy at Bank Sampah Amal Haqiqi was significant but remained highly dependent on community engagement and technical support. To ensure sustainability, management strategies should have prioritized strengthening social participation and upgrading technical facilities to further reduce residue levels.